Axiological Orientations of Participants of Educational Relationships: Social-Psychological Aspect - Irina V. Serafimovich; Olga A. Belyaeva (National Research Mordova State University, 2019)
Introduction. The relevance of the research is determined by high public concern with the educational sphere, especially the area of developing secondary school learners' personal results that have the form of the system of value-oriented attitudes and settings. Further self-education, personal growth, self-identification and community commitment on the whole depend on them. The authors for the first time attempted to estimate systemically axiological aspects of the social and cultural context of the modern educational environment. Their objective was to reveal the specifics of axiological orientation systems and to determine the degree of uniformity and congruence of information axiological field of participants involved in various educational relations. Materials and Methods. Senin's core values questionnaire was used to examine the value orientation of university teaching staff and graduates; the personal growth questionnaire by D. V. Grigorev, I. V. Kuleshova, P. V. Stepanov was used to study high school students' value-based attitude to several significant objects; mathematical and statistical methods of data processing were ap plied. Results. On the basis of revealed general and specific qualities of the value system of educational relationship participants, one can conclude that teenagers develop criticism in estimation of most real-world objects and tension in perception of subject-subject relations and their own personalities. The authors found that teachers with different work experience select spheres with high and low status in a similar way. Discussion and Сonclusion. This range of problems is to be further investigated in longitudinal studies devoted, in particular, to the estimation of congruence of values of all participants engaged in educational relationship. The obtained results can be used to choose strategies of psychological, pedagogical and tutor support of teenagers and teachers and to define new priorities of continuous teacher training.